Factores asociados al resultado de amputaciones transtibiales en pacientes diabéticos de un hospital referencial de la Amazonia Peruana 2023-2024 - Paliza Lopez, Oliver Uri (2024)
Introduction: Diabetes mellitus is a chronic condition with high incidence and morbidity and mortality rates worldwide. Long-term complications, such as diabetic neuropathy and peripheral arterial disease, can lead to foot ulcers and, in severe cases, amputations. This study will focus on the factors associated with the outcome of transtibial amputations in diabetic patients at a referral hospital in the Peruvian Amazon, specifically in the Loreto region. Objective: To determine the factors associated with the outcome of transtibial amputations in diabetic patients at a Referral Hospital in the Peruvian Amazon during 2023-2024. Method: An analytical, quantitative, cross-sectional, and retrospective methodological design will be employed. Population: The study population consists of 148 diabetic patients with transtibial amputations at the Regional Hospital of Loreto during the 2023-2024 period. The sample will be 106 patients, calculated using the finite population formula. Results: Data processing and analysis will be conducted using SPSS v29 software. Univariate and bivariate analyses will be applied, using statistical tests such as Chi-square and Student's t-test, in addition to multivariate analysis through multinomial logistic regression, with a significance level of 95%. Conclusion: The study aims to identify key variables that influence surgical and postoperative outcomes of transtibial amputations in diabetic patients. The findings will be essential for developing more effective management strategies and improving clinical outcomes and the quality of life for these patients.